Evaluation of Operational Resilience in Cyber-Physical Production Systems: literature review. Issue 10 (2022) - Attajer, Ali; Chaabane, Sondes; Darmoul, Saber; Sallez, Yves; Riane, Fouad
Abstract: In Cyber-Physical Production Systems, smart production resources (e.g., augmented operators, machines, products) can collaborate according to innovative, adaptive, and autonomous ways. This context offers new methods and tools to deal with disturbances and operational risks effectively and efficiently. In such environments, resilience engineering aims to improve the systems' abilities and capabilities to face disturbances and operational risks, and to be restored to safe behaviors, acceptable levels of performance and quality of service. Despite an increasing interest in operational resilience, and despite the importance of this topic in both research and industrial practice, there is no literature review and analysis to synthesize works and to identify the main issues encountered in this field. This article fills in this gap and shows that there are six main research streams in operational resilience.